PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA CHEMOPOLY GAME DAN TOURNAMENT QUESTION CARDS - Dui Sherly Viani; Amrul Bahar; Elvinawati Elvinawati (University of Bengkulu, 2017)
The low learning outcomes of the students is because in the learning process of teacher and student interaction only goes one way. Teachers often use lecture methods so that students tend to only accept what is given. This can make the students' motivation and activeness in following the lesson to be low. Therefore, researchers try to vary the cooperative learning model using Chemopoly Game media and Tournament Question Cards. This is quasi experimental research with population class X MIPA in SMAN 2 Kota Bengkulu and sample is class X MIPA C using media Tournament Question Cards and class X MIPA D using Chemopoly Game media. Data analysis used were mean score, normality test, homogeneity test, and t test. The average posttest grade of experiment I is 85,59 While for experiment class II is 79,38. Then t test and obtained tcount> ttable (2.62> 2.38). The results of this study indicate that there is a significant difference between student learning outcomes using Chemopoly Game media and Tournament Question Cards on basic chemical law materials.